Modelling and characterization of a string under high tension - Rutah, Eshvin (2018)
This project aims to model and characterise the behaviour of a racket string when it is hit by a tennis ball. The results will help to decide whether it is possible to use larger strings under high tension and highly damped conditions on the walls of tall buildings to prevent human fatalities during the cleaning of the exterior of windows or damp the motion of objects to stop them from falling away. In the laboratory, the string was clamped under high tension and a high-speed camera was used to record the impact of the ball on the string. The videos were then analysed and the maximum deflection of the string when the ball reaches instantaneous velocity was determined. The author compared the experimental results with the theoretical approximations and found out there is a large error between these two.